Outcomes of Patients with Malignancy Admitted to the Intensive Care Units: A Prospective Study - Hazem I. Assi; Nour Abdul Halim; Ibrahim Alameh; Jessica Khoury; Vicky Nahra; Fares Sukhon; Maya Charafeddine; Clara El Nakib; Nour Moukalled; Maroun Bou Zerdan; Pierre Bou Khalil (Critical Care Research and Practice)
Introduction. Decisions regarding whether advanced cancer patients should be admitted to the ICU are based on a complex suite of considerations, including short- and long-term prognosis, quality of life, and therapeutic options to treat cancer. We aimed to describe demographic, clinical, and survival data and to identify factors associated with mortality in critically ill advanced cancer patients with nonelective admissions to general ICUs. Materials and Methods. Critically ill adult (≥18 years old) cancer patients nonelectively admitted to the intensive care units at the American University of Beirut Medical Center between August 1st 2015 and March 1st 2019 were included. Demographic, clinical, and laboratory data were prospectively collected from the first day of ICU admission up to 30 days after discharge. This study was strictly observational, and clinical decisions were left to the discretion of the ICU team and attending physician. Results. 272 patients were enrolled in the study between August 1st 2015 and March 1st 2019, with an ICU mortality rate of 43.4%, with the number rising to 59% within 30 days of ICU discharge. The mean length of stay in our ICU was 14 days (IQR: 1–120) with a median overall survival of 22 days since the date of ICU admission. The major reasons for unplanned ICU admission were sepsis/septic shock (54%) and respiratory failure (33.1%). Cox regression analysis revealed 7 major predictors of poor prognosis. Direct admission from the ED was associated with a higher risk of mortality (48.9%) than being transferred from the floor (32.6%) (p=0.014). Conclusion. Our study has shown that being directly admitted to the ICU from the ED rather than being transferred from regular wards, developing AKI, sepsis, MOF, and ARDS, or having an uncontrolled malignancy are all predictive factors for short-term mortality in critically ill cancer patients nonelectively admitted to the ICU. Vasopressor use and mechanical ventilation were also predictors of mortality.